THE HISTOPATHOLOGICAL CHANGES OF PLACENTA IN HYPERTENSIVE DISORDERS OF PREGNANCY AND THEIR CORRELATION WITH FETAL OUTCOME: A CROSS-SECTIONAL STUDY - Panday, Aakriti; Budania, Suman; Bano, Tanu (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objective of this study was to evaluate the histopathology and establish the correlation between placental changes in hypertensive disorders of pregnancy and fetal outcome. Methods: A cross-sectional study included 100 pregnant women with singletons admitted to the labor room with gestational ages >30 weeks and 35 weeks with hypertensive disorders of pregnancy between December 2021 and November 2022, admitted to the Department of Obstetrics and Gynecology, Sardar Patel Medical College, Bikaner. Shape of placenta, weight in grams, size, diameter in centimeters, and deposition were examined. Fetomaternal outcome was also noted. Results: Eighty percent (80) were in the age group of 21–30 years, with a mean age of 25.01±4.56 (range: 18–44 years). Only 35% of females were booked, and 63% of cases belonged to G1. Maximum cases were of pregnancy-induced hypertension (42%), followed by eclampsia (36%) and pre-eclampsia (16%), and the minimum case belonged to HELLP (1%). Although cases of placental infarction were higher in neonatal intensive care unit (NICU) admitted cases as compared to non-admitted cases (61.19% vs. 45.45%, respectively), calcification was higher in NICU-admitting cases as compared to non-admitting cases (95.52% vs. 84 vs. 5%, respectively). Syncytial knots were 94.03% vs. 81.82%, respectively, and grade fibrosis was 44.78% vs. 27.27%. Fibrinoid necrosis (71.64% vs. 54.55%) and leukocytic infiltration (68.66% vs. 63.64%). Statistically, no significant difference was observed in all parameters. Conclusion: Placental morphology and histopathology are affected in hypertensive pregnancies, which might be the reason for placental insufficiency in these cases.